1980
DOI: 10.1063/1.328205
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of optical strip waveguides with nearly circular cross section by silver ion migration technique

Abstract: Circular optical waveguides have been fabricated from vacuum-deposited Ag layers by ion migration technique into soda-lime substrate glass. In this method two different guide patterns, one of which is the mirror image of the other, are made. Later the guide patterns are placed on top of each other and circular guides are thus obtained. The ends of the guides are studied by optical microscope and the near-field scanning method. The optical loss spectrum is measured from 450 to 1600 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…By the pertubation method in WKB approximation, we can get the coupling length for the m-th mode (1) Here L m is given by (A7) and can be interpreted as the By the pertubation method in WKB approximation, we can get the coupling length for the m-th mode (1) Here L m is given by (A7) and can be interpreted as the…”
Section: Coupling Length Of a Prism Couplermentioning
confidence: 99%
See 1 more Smart Citation
“…By the pertubation method in WKB approximation, we can get the coupling length for the m-th mode (1) Here L m is given by (A7) and can be interpreted as the By the pertubation method in WKB approximation, we can get the coupling length for the m-th mode (1) Here L m is given by (A7) and can be interpreted as the…”
Section: Coupling Length Of a Prism Couplermentioning
confidence: 99%
“…During last years, there has been growing interest in highly multimode graded-index waveguides in glass substrates with small index increase on the surface [1,2]. It is mostly due to their potential use in waveguide devices compatible with multimode fiber-optical communication systems.…”
Section: Introductionmentioning
confidence: 99%
“…These elements cooperate with fiber waveguides. Hence the need to optimize the distribution of refraction of channel waveguides in terms of minimizing the loss of optical power at their connections with fiber waveguides [52,53]. In addition to the passive elements of planar optics, the laser structures and optical amplifiers can also be produced by the ion exchange method.…”
Section: Applications Of Producing Gradient Refractive Index In Glassmentioning
confidence: 99%
“…Nearly circular strip waveguides were demonstrated by Viljanen and Leppihalme using such a "dry" process along with thermal annealing. 28 Targeting multimode waveguides also brought added interest in field-assisted fabrication processes, which could provide almost step-index profiles. Subsequent work by Lilienhof et al showed that profile shapes were primarily determined by the electric field distribution in glass.…”
Section: Early Years Of Ion-exchanged Waveguidesmentioning
confidence: 99%
“…24 Figure 1(b) illustrates the field-assisted ion migration from a molten salt at the anode side. 21 Figure 1(c) is the field-assisted migration from a metal thin film source; 28 the thin film may be deposited on top of a patterned mask, or it can be directly patterned onto the glass surface. Figure 1(d) shows a field-assisted migration process, combining a patterned metal film with molten salt source at the anode surface; 45,46 this can be used as a one-step process for producing buried waveguides, for after the metal film source has been consumed, this will directly continue as a field-assisted burial, similar to configuration [ Fig.…”
Section: Waveguide Fabrication Processesmentioning
confidence: 99%